Horizontes de significado y metamorfosis óntica: sobre el destino de un diálogo roto - Juan, Blanco Ilari (Universidad de San Buenaventura - Cali, 2017)
In this paper the gap between philosophical discourse and common language was analyzed. The general thesis sustains that the horizon of meaning in which we operate commits us with an ontology that sometimes contradicts ontology unveiled by the objective view. For the contrasting of this hypothesis I followed a critical semantic and pragmatic method of some main categories in the debate. This methodology drove me to put in relationship heterogeneous universes of discourse. I take some examples in which that distance is evident and irreconcilable: Heidegger and his notion of “meaning,” “facticity” and “world.” Taylor and the change subject aporia, among others. I want to emphasize the impossibility of finding a common ground in which these “worlds” can find each other. The general tone of the work is a plea for the discursive plurality, of the irreducibility of common knowledge, doxastic, to scientific epistemic discourse.